Bridging constructions - Guérin, Valérie (Studies in Diversity Linguistics, 2019)
Many descriptive grammars report the use of a linguistic pattern at the interface between discourse and syntax which is known generally as tail-head linkage. This volume takes an unprecedented look at this type of linkage across languages and shows that there exist three distinct variants, all subsumed under the hypernym bridging constructions. The chapters highlight the defining features of these constructions in the grammar and their functional properties in discourse. The volume reveals that: Bridging constructions consist of two clauses: a reference clause and a bridging clause. Across languages, bridging clauses can be subordinated clauses, reduced main clauses, or main clauses with continuation prosody. Bridging constructions have three variants: recapitulative linkage, summary linkage and mixed linkage. They differ in the formal makeup of the bridging clause.